Polysomnography in preterm infants with perinatal pathology: first 5-year experience in Ukraine - Dariia Kostiukova; Anastasiya Babintseva; Thomas Erler; Yelyzaveta Shunko; Maksym Roziaiev (Hygeia Press di Corridori Marinella, 2021)
Background: Polysomnography (PSG) is an important component in comprehensive neuromonitoring that allows timely evaluation of the sleep maturation quality and diagnosis of Sleep-Related Breathing Disorders (SRBD) in preterm infants (PIs). Aim: To determine PSG indices in PIs of different gestational age with perinatal pathology. Methods: This was the first original single-center observational study conducted in Ukraine. The groups of observation consisted of a total of 61 PIs with perinatal pathology: 16 infants of 24-28 weeks (Group I), 33 infants of 29-32 weeks (Group II), and 12 infants of 33-36 weeks (Group III). Non-parametric methods were used for statistical analyses. Results: A maximum level of Respiratory Disturbance Index during Quiet Sleep (pI-II = 0.016, pI-III = 0.014), and Respiratory Disturbance Index Total and Respiratory Disturbance Index during Active Sleep was found in Group I with an average postmenstrual age (PMA) of 36 weeks, as well as a maximum frequency of SRBD with predominance of hypopnea and obstructive apnea. A statistically valuable decrease in Respiratory Disturbance Index during Quiet Sleep was determined in Group II with an average PMA of 35 weeks, with a stable decrease in all other indices. Minimum values were found in of all the PSG indices in Group III with an average PMA of 38 weeks. Mean values of Arousal Index in all the groups of observation were higher than 20. The minimum level of oxygen saturation during SRBD was diagnosed in infants from Group I (pI-III = 0.0072). Conclusions: Disorders of physiological sleep formation and pathological respiratory events during sleep were found in the majority of PIs with perinatal pathology, which stipulates the necessity to conduct careful monitoring of vital functions and differential treatment of various apnea types.